ANALYSIS AND REVIEW OF PRESCRIBING CLINICAL DECISION SUPPORT SYSTEM WITHIN THE CONTEXT OF NHS SECONDARY SECTOR - Al-Garni, Bandar Mohammad (LIFE: International Journal of Health and Life-Sciences, 2018)
Clinical Decision Support System (CDSS) is an important and emerging area of research. Therefore, the study of CDSS form an important field of information technology (IT) used in health care industry. Diagnosis and decision making form an integral part of CDSS. Based on the healthcare data and patient’s medical history, CDSS performs recommendation, which helps healthcare professionals to diagnose properly and make clinical decisions accordingly. In this paper, we present analysis and review of prescribing CDSS within the context of the secondary sector of the United Kingdom (UK) National Health Service (NHS). It was observed that prescribing CDSS enhances the safety of patients by reducing medication errors that occur during traditional prescribing (non-electronic prescribing). The reduction of medical errors is due to the efficiency of prescribing CDSS in facilitating health care providers with a holistic view of patient health records and any drug allergy or drug-drug interactions. This study showed that successful adoption of CDSS within the NHS secondary sector faces challenges such as physician acceptance, training, and interoperability.